1,2,4-Triazine Chemistry Part II: Synthetic approaches for phosphorus containing 1,2,4-triazine derivatives - Abdel-Rahman, Reda Mohammady; Ibrahim, Magdy Ahmed; Ali, Tarik El-Sayed (European Journal of Chemistry, 2010)
This review represents the methods developed for the synthesis of phosphorus containing 1,2,4-triazine moieties. These methods depends on the phosphorylation of side functional groups of 1,2,4-triazines and cyclization of side functional groups of 1,2,4-triazines with phosphorus reagents to give isolated and fused phosphorus heterocyclic systems.